PENGARUH DIGITAL MARKETING CAPABILITY DAN CUSTOMER ENGAGEMENT TERHADAP KINERJA PEMASARAN UMKM (STUDI PADA UMKM SEKTOR KULINER DI KOTA KENDARI) - Dzulfikri Azis Muthalib; Abd Azis Muthalib; Laode Asfahyadin Aliddin; Ambo Masse (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze the effect of digital marketing capability and customer engagement on the marketing performance of culinary MSMEs in Kendari City, both partially and simultaneously. This research employs a quantitative approach with an explanatory research design. Data were collected through a survey using structured questionnaires distributed to owners or managers of culinary MSMEs in Kendari City. The data were analyzed using multiple linear regression analysis. The results indicate that digital marketing capability has a positive and significant effect on marketing performance. Customer engagement also shows a positive and significant influence on marketing performance. Simultaneously, digital marketing capability and customer engagement complement each other and play an important role in enhancing the marketing performance of culinary MSMEs. These findings highlight the importance of integrating digital marketing capabilities with effective customer engagement strategies to improve competitiveness and ensure the sustainability of culinary MSMEs in the digital era.